The Influence of Problem Based Learning Model on Students' Concept Understanding of Heat Material - Leza Puastri Putri; Johana Aulina Rahmatin (Indonesian Publication Center, 2025)
The results of initial observations conducted by researchers at SMAN 2 Praya showed that conceptual understanding of heat material was still relatively low. This is because students are less interested in learning through lecture methods or other conventional methods. This research is a quantitative research using a quasi-experimental method. The population in this study were grade XI students of SMAN 2 Praya Phase F. The research sample was selected by purposive sampling, with class F1-1 as the control group and class F1-2 as the experimental group. The research instrument used to measure conceptual understanding was a multiple-choice test of 15 questions that had been tested for validity, reliability, difficulty level, and discriminating power. The post-test results of the experimental and control groups were analyzed for normality and homogeneity, then a hypothesis test (ANOVA test) wascarried out. The results of the study showed a significance value of 0.00 so that it can be concluded that there is an influence of the Problem Based Learning model on students' conceptual understanding of heat material.